Утопія як проективна інтелектуальна конструкція - Петрушенко, Оксана (Видавництво Львівської політехніки, 2014)
Автор статті стверджує, що тривале існування утопічної думки пояснюється її зв’язком з важливими потребами існування людини та діяльності людської свідомості – сферою ідеалізації, інтелектуального конструювання, уявленнями про належне та бажане, детермінованістю людського життя майбутнім, прогнозуванням, прагненням уникнути антиномій реального життя. У цьому контексті аналізуються концепції: утопічного реалізму Е. Гідденса, принципу відповідальності Г. Йонаса, реалістичної утопії Ю. Габермаса. The paper explains a long-time existence of utopian thinking as a result of its connection with the important needs of human existence and consciousness activity. Utopia is closely connected with the sphere of idealisation. It is the ability of man’s consciousness to create some intellectual constructions describing internal relations which are important but cannot be perceived with the sense organs. At the end of the 20th century utopia is studied in the context of social constructivism that seeks to create the image of social reality in accordance with some logical arguments (utopian constructivism). Utopian thought is also related to the ideas of appropriateness and desirability investigated by the philosophers since the 19th century. The author claims that human life is determined by the future and utopia is closely connected with this tendency. A well-known philosopher E. Bloch investigates utopia analysing the concepts of hope and prognostics. In his view, utopia fulfills the role of long-range prognostics that shows us the true values of mankind. According to K. Jaspers, people like utopia because it allows them to see the world without any problems and difficulties and avoid antinomies of real life. The philosopher criticizes utopia thinking that real life without antinomies can be characterised by a lack of energy for further growth. A. Giddens pays attention to a special role of utopia in the period of globalisation. The thinker believes that utopia is quite useful as a project of the future development of humanity. In his opinion, it must be connected with realism because in the modern world every country can plan its future only in the context of the common development of humankind. Taking into consideration the above-mentioned fact, A. Giddens uses the term “utopian realism”. Both the principle of responsibility offered by G. Yonas and realistic utopia suggested by U. Habermas are analysed in the given context.
Utopia as a projective intellectual construction
Keywords: утопія; утопічна свідомість; інтелектуальне конструювання; прогнозування; utopia; utopian consciousness; intellectual constructing; prognostics